Reconstruction of large tibial bone defects following osteosarcoma resection using bone transport distraction: A report of two cases - Yang, Zhengming (Oncol Lett, 2016)
The clinical efficiency of bone transport distraction osteogenesis in the reconstruction of large tibial defects following resection of osteosarcoma remains unclear. The current study presents two cases of large tibial defects treated with bone transport distraction using an Orthofix external fixator. Case 1 was a 29-year-old man with a tibial defect 11 cm in length, while case 2 was a 16-year-old girl with a 15-cm-long defect. Bone transport distraction osteogenesis was initiated for the both cases on day 14 following resection of the tibial osteosarcoma. Bone transport distraction in case 1 and 2 was continued for 16 and 28 months, respectively, and the patients were followed up for 51 and 56 months, respectively. The two patients did not exhibit any signs of tumor recurrence or tumor metastasis during the follow-up period. The Musculoskeletal Tumor Society functional scores at final follow-up visits were 22 and 18 for case 1 and 2, respectively. Based on the experience gained in these 2 cases, a bone transport is a viable option for the reconstruction of large tibial defects following osteosarcoma resection.